2000
DOI: 10.1093/emboj/19.12.2924
|View full text |Cite
|
Sign up to set email alerts
|

A phosphoserine-regulated docking site in the protein kinase RSK2 that recruits and activates PDK1

Abstract: The 90 kDa ribosomal S6 kinase-2 (RSK2) is a growth factor-stimulated protein kinase with two kinase domains. The C-terminal kinase of RSK2 is activated by ERK-type MAP kinases, leading to autophosphorylation of RSK2 at Ser386 in a hydrophobic motif. The N-terminal kinase is activated by 3-phosphoinositidedependent protein kinase-1 (PDK1) through phosphorylation of Ser227, and phosphorylates the substrates of RSK. Here, we identify Ser386 in the hydrophobic motif of RSK2 as a phosphorylationdependent docking s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
271
0
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 282 publications
(285 citation statements)
references
References 48 publications
(73 reference statements)
10
271
0
1
Order By: Relevance
“…MSK1 was originally identified [14] through a search for novel AGC kinases that might be regulated by PDK1 (phosphoinositide-dependent kinase 1), a 'master' kinase required for the activation of a subset of AGC kinases including RSK. PDK1 acts by phosphorylating a specific residue in the T-loop of its substrates, and the phosphorylation of this site is essential for kinase activation [18][19][20]. Work using PDK1 −/− embryonic stem cells confirmed that PDK1 was required for the activation of RSK1, RSK2 and RSK3 [20].…”
Section: Introductionmentioning
confidence: 99%
“…MSK1 was originally identified [14] through a search for novel AGC kinases that might be regulated by PDK1 (phosphoinositide-dependent kinase 1), a 'master' kinase required for the activation of a subset of AGC kinases including RSK. PDK1 acts by phosphorylating a specific residue in the T-loop of its substrates, and the phosphorylation of this site is essential for kinase activation [18][19][20]. Work using PDK1 −/− embryonic stem cells confirmed that PDK1 was required for the activation of RSK1, RSK2 and RSK3 [20].…”
Section: Introductionmentioning
confidence: 99%
“…Akt and RSK1 share some common substrates and both can be regulated by PDK1 (Alessi et al, 1997). While RSK and Akt are both substrates of PDK1, recruitment of PDK1 by RSK2 was shown to cause phosphorylation and activation of PDK1 that in turn would activate both Akt and RSK2 again illustrating a close relationship between RSK and Akt activation (Frodin et al, 2000).…”
Section: Discussionmentioning
confidence: 89%
“…The proteins, that mediate KGF-induced Akt activation, however, are not known. It was recently shown that RSK2, a member of the RSK family of proteins recruits PDK1 and promotes coordinated phosphorylation and activation of PDK1 and RSK2 (Frodin et al, 2000). PDK1 is a kinase that is critical for the activation of Akt and related enzymes, including RSK, that regulate many physiological processes such as cell survival, proliferation, and gene expression.…”
Section: Rsk1 Is Required For Akt Activation By the Kgfrmentioning
confidence: 99%
See 1 more Smart Citation
“…However, Src, Fyn, and Abl tyrosine kinases have been shown to phosphorylate PDK1 in vitro and overexpression of v-Src in mammalian cells results in tyrosine phosphorylation and activation of PDK1 [15][16][17]. In addition, mammalian PDK1 is affected by interactions with PDK1-associating proteins, including PKC-related kinase 1 (PRK1), and Hsp90 [18][19][20][21], suggesting that its activity is controlled by interactions with other proteins as well. Furthermore, human PDK1 has been shown to interact with 14-3-3 h and g and a 14-3-3 recognition site has been identified at Ser-241 [22].…”
Section: Introductionmentioning
confidence: 99%